Cannabinoids in oral fluid following passive exposure to marijuana smoke - Moore, Christine; Coulter, Cynthia; Uges, Donald; Tuyay, James; van der Linde, Susanne; van Leeuwen, Arthur; Garnier, Margaux; Orbita, Jonathan (Forensic science international, 2011)
The concentration of tetrahydrocannabinol (THC) and its main metabolite 11-nor-Δ 9-tetrahydrocannabinol-9-carboxylic acid (THC-COOH) as well as cannabinol (CBN), and cannabidiol (CBD) were measured in oral fluid following realistic exposure to marijuana in a Dutch coffee-shop. Ten healthy subjects, who were not marijuana smokers, volunteered to spend 3 h in two different coffee shops in Groningen, The Netherlands. Subjects gave two oral fluid specimens at each time point: before entering the store, after 20 min, 40 min, 1 h, 2 h, and 3 h of exposure. The specimens were collected outside the shop. Volunteers left the shop completely after 3 h and also provided specimens approximately 12–22 h after beginning the exposure. The oral fluid specimens were subjected to immunoassay screening; confirmation for THC, cannabinol and cannabidiol using GC/MS; and THC-COOH using two-dimensional GC–GC/MS. THC was detectable in all oral fluid specimens taken 3 h after exposure to smoke from recreationally used marijuana. In 50% of the volunteers, the concentration at the 3 h time-point exceeded 4 ng/mL of THC, which is the current recommended cut-off concentration for immunoassay screening; the concentration of THC in 70% of the oral fluid specimens exceeded 2 ng/mL, currently proposed as the confirmatory cut-off concentration. THC-COOH was not detected in any specimens from passively exposed individuals. Therefore it is recommended that in order to avoid false positive oral fluid results assigned to marijuana use, by analyzing for only THC, the metabolite THC-COOH should also be monitored.